Trauma Theory and Recovery in Amy Tan’s Selected Novels Based on Judith Herman’s Theory (Scientific Journal of Research Studies in Future Psychology, 2024)
This essay is an attempt to study Amy Tan’s in the light of Judith Herman’s theory of trauma and recovery. As Herman puts it, traumatic event "overwhelms the ordinary human adaptations to life. "Unlike commonplace misfortunes," she writes, "traumatic events generally involve threats to life or bodily integrity, or a close personal encounter with violence and death.". Injury is an object of study in different parts of the scholarly world: the inherent sciences, the sociologies, and the humanities; subsequently, injury has a troublesome and confusing relationship to interdisciplinary investigations. Injury research has late been situated in a few fields of study across the institute, including brain science, psychiatry, social science, history, general wellbeing, and writing.  As indicated by the scholars in injury review, declaration of the horrible experience happens throughout the entire existence of the damaged subject's life, however, the portrayal of the previous occasion in the current matters to them. Hence, this theory concentrates on the awful experience's ramifications and portrayals in the characters' familial and public activity after they experience horrendous accidents. One of these outcomes is the spilt subjectivity and illusive personality of the characters which influences various parts of their daily routines and associations with individuals experiencing around them. Thusly, the decision for these books depends on the way that it by and large covers a wide scope of speculations in injury studies.